Applications of nuclear magnetic resonance in lipid analyses: An emerging powerful tool for lipidomics studies - Li, Jingbo; Vosegaard, Thomas; Guo, Zheng (Progress in lipid research, 2017)
The role of lipids in cell, tissue, and organ physiology is crucial; as many diseases, including cancer, diabetes, neurodegenerative, and infectious diseases, are closely related to absorption and metabolism of lipids. Mass spectrometry (MS) based methods are the most developed powerful tools to study the synthetic pathways and metabolic networks of cellular lipids in biological systems; leading to the birth of an emerging subject lipidomics, which has been extensively reviewed. Nuclear magnetic resonance (NMR), another powerful analytical tool, which allows the visualization of single atoms and molecules, is receiving increasing attention in lipidomics analyses. However, very little work focusing on lipidomic studies using NMR has been critically reviewed. This paper presents a first comprehensive summary of application of 1H, 13C &31P NMR in lipids and lipidomics analyses. The scientific basis, principles and characteristic diagnostic peaks assigned to specific atoms/molecular structures of lipids are presented. Applications of 2D NMR in mapping and monitoring of the components and their changes in complex lipids systems, as well as alteration of lipid profiling over disease development are also reviewed. The applications of NMR lipidomics in diseases diagnosis and food adulteration are exemplified.